Diana Šileikaitė. Immanuel Kant as a Pedagogue - Šileikaitė, Diana (Acta Paedagogica Vilnensia, 2002)
The present article aims to present the pedagogical activity of the famous German philosopher of the 18th century Immanuel Kant (1724-1804) by means of theoretical analysis supplied in the relevant literature and the data materials of historical sources. It attempted to prove that Immanuel Kant was active not only as a theorist, but also as practitioners in the field of pedagogy. In terms of the experiences of Kant in the field of theory and practice of education the two research moments are to be emphasized, namely Kant’s work as a Hofmeister (1747-1755) in Judtschen, Amsdorf and Rautenburg, and his work as a lecturer at the University Königsberg (1755-1796). In the presentation of Immanuel Kant’s work as a lecturer at the University of Konigsberg is among other things to the establishment of his lectures, his teaching methods, received their connection with Kant’s theoretical works, as well as some aspects of his personality that are important for an educator of such significance.